Sustainability Standards, Gender, and Nutrition among Smallholder Farmers in Uganda. Issue 9 (1st September 2016) - Chiputwa, Brian; Qaim, Matin
Abstract: Sustainability standards are gaining in importance in global markets for high-value foods. While previous research has shown that participating farmers in developing countries may benefit through income gains, nutrition impacts have hardly been analysed. We use survey data from smallholder coffee farmers in Uganda – certified under Fairtrade, Organic, and UTZ – to analyse impacts on food security and dietary quality. Estimates of instrumental variable models and simultaneous equation systems show that certification increases calorie and micronutrient consumption, mainly through higher incomes and improved gender equity. In certified households, women have greater control of coffee production and monetary revenues from sales.